(untitled) (Estudios Sociales, 2025)
Our contribution aims to explain the motives and strategies used by the main actors of Neuquén radicalism and frepasism in the assembly of an alliance with the objective of challenging the predominant provincial party for the governorship. Organized in line with national actions, this political play meant a strong challenge to face a stable government represented by the Neuquén Popular Movement, anchoring in the possibility of defeating it. Nevertheless, it was also difficult to the local force which had a divided government for the first time in its history. Yet, it overcame the difficulties by fragmenting and co-opting opposition legislators. The axis of analysis involves exposing the course of the only historical moment since the return of democracy, in which the opposition was closer to achieving alternation in the province. The temporal cut of the research links the time that passes between 1999 and 2003 and links local-national studies, documentation from personal archives, regional-national press and key oral testimonies of the chosen period.